PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP JUMLAH SEL NEURON DI CEREBELLUM Rattus norvegicus BARU LAHIR - Herlina Alvianti N (NHM PRESS, 2019)
Efforts could be made to improve human resources that have intelligence required a positive relationship between health and good education quality, one of the efforts to improve human resources requires good brain quality since the phase of conception. Classical music has been shown to boost brain function and human intellectual optimally believed to have the best stimulating effect on babies. Cellular exposure to Mozart affects the number of more neuronal cells. Analyze the number of cerebrum and cerebellum neuronal cells of newborn Rattus norvegicus between the exposed to Mozart music, Beethoven, Chopin and not exposed to music during pregnancy. This research was an experimental research with posttest only control group design. The sample was divided into four groups randomly, non-exposed, Mozart music exposure group, Beethoven music exposure group, Chopin music exposure group, exposed for 1 hour during the night after Rattus norvegicus was pregnant on day-10 with an intensity of 65 dB and a distance of 37 cm from the rat cage. On the 20th day of the pregnant mother of Rattus norvegicus was sacrificed and selected two of Rattus norvegicus's babies with the greatest weight and then the brains of Rattus norvegicus's babies were decapitated and brain dissection to count the number of neuronal cells with Hemotoxyln-Eosin staining. The statistical results showed that the number of neurons of cerebellum cells in the Mozart group differed significantly from Beethoven, Chopin and not exposed to music with p <0.05. The number of neuronal cells of cerebellum of the newborn Rattus norvegicus who exposed to Mozart music during pregnancy proved higher than that exposed to Beethoven music, Chopin and not exposed to music